Optimization and in-vivo evaluation of isradipine nanoparticles using Box-Behnken design surface response methodology - Vijayan Venugopal; K. Jayaraja Kumar; S. Muralidharan; S. Parasuraman; P. Vasanth Raj; K. Venkates Kumar (Elsevier, 2016)
The isradipine is the potent anti hypertensive drug, which is matrix in polymeric nanoparticle by using solvent evaporation method. In this work, 3-factor, 3-level Box-Behnken design was used to optimize the process parameters like polymer concentration (A), sonication frequency (B) and sonication time (C). Three dependent variable's particle size, entrapment efficiency and practical yield were measured as responses. Mathematical equations and response surface plots were used to relate the dependent and independent variables. The optimization model of particle size of 343.14 nm, entrapment efficiency of about 83.74% and practical yield of 85.39% with A, B and C levels of 750 mg, 37.5 min and 40 kHz respectively. The observed responses were in close agreement with the predicted values of the optimized process. The prepared nanoparticle was characterized by Fourier transform infrared spectroscopy, morphological studies and in-vitro drug release studies. The prepared nanoparticle was showed good sustained release of drug upto 24 h. The anti-hypertensive study was performed on animal model. The PMMA (Poly-Methyl-Metha- Acrylate) isradipine nano particle shows fall in blood pressure was delayed and reach 152±2 mmHg at 1 h. The action was sustained until prolong period. Based on pharmacokinetic and pharmacodynamics parameter, the isradipine nanoparticles shows better bioavailability compare with solution form.